VARIASI GERAKAN RADIKAL ISLAM DI INDONESIA - Rubaidi, Rubaidi (Universitas Islam Negeri Raden Intan Lampung, 2011)
Islamic radical movements in Indonesia are various. Their slogans about Islamic union are refutable by heteroginities of groups and pattern of movements. This article portrays about their variety of movements. Broadly speaking , these groups are divided into two models. First, Islamic radical movements from their origins, such as HTI, Tarbiyah-Ikhwanul Muslimin and Orthodox-Wahabi Movement. Second, Islamic radical movements which have been metamor phosis, though ideologically they are in line with transnational Islamic radical movements in the Middle East. Examples of the second model are among others Front Pembela Islam (FPI), Laskar Jihad (LJ), Majelis Mujahidin Indonesia (MMI). These groups make Indonesian Islam more discursive in terms of their contestation in gaining supports from Muslims in Indonesia.